Prediction of channel sandbody distribution in the lower section of Sifangtai Formation at the southern end of Chang Placanticline in Songliao Basin - Zhu Wenping (E3S Web of Conferences, 2021)
The channel sand bodies in the lower section of the Sifangtai Formation in the Songliao Basin are rich in uranium resources. The development of channel sand body distribution prediction is of great significance for guiding the exploration of sandstone-type uranium deposits. In this study, the wave-indicated inversion technology was used to predict the thickness of the sand body, the root mean square amplitude attribute was used to identify the plane shape of the river channel, and the seismic facies analysis and tracking technology of the section was used to identify the channel period and finely describe the channel distribution. The results show that there are two stages of channel sand bodies in the lower part of Sifangtai Formation, and the sand bodies are distributed in a wide range. The maximum thickness of single stage sand bodies is about 15m, with an average of 8 meters. The thickness of the sand body where the two phases of the river are superimposed is the largest, up to 28m, which is a favorable ore-bearing location revealed by current exploration.